Language-specific hotspots of interest in IUCN Red Listed terrestrial mammals - Siljander, Mika; Di Minin, Enrico; Ladle, Richard J.; Correia, Ricardo A. (TAYLOR & FRANCIS LTD, 2025)
Biodiversity conservation continues to be a global priority and insights into societal interest and support for targeted species conservation actions are essential for their success. Taking advantage of emerging culturomics methods, here we propose a new methodology for mapping societal interest towards terrestrial mammals by combining the IUCN Red List range maps with indicators of societal interest towards species derived from Wikipedia pageviews data for different languages. We show that societal interest towards terrestrial mammals varies between different language groups and is not necessarily concentrated in areas of high biodiversity. We propose that our mapping method can help to identify hot- and cold-spots of societal interest towards biodiversity for different taxonomic and language groups, and we discuss potential conservation applications of the proposed mapping method.